Stopping Tumor Necrosis Factor Inhibitor Treatment in Patients With Established Rheumatoid Arthritis in Remission or With Stable Low Disease Activity: A Pragmatic Multicenter, Open‐Label Randomized Controlled Trial. Issue 8 (27th July 2016) - Ghiti Moghadam, Marjan; Vonkeman, Harald E.; ten Klooster, Peter M.; Tekstra, Janneke; van Schaardenburg, Dirkjan; Starmans‐Kool, Mirian; Brouwer, Elisabeth; Bos, Reinhard; Lems, Willem F.; Colin, Edgar M.; Allaart, Cornelia F.; Meek, Inger L.; et al.
Abstract : Objective: Tumor necrosis factor inhibitor (TNFi) biologic agents are an effective treatment for rheumatoid arthritis (RA). It is unclear whether patients whose disease is in remission or who have stable low disease activity need to continue use of TNFi or can stop this treatment. This study was undertaken to assess whether patients with established RA who are in remission or have stable low disease activity can effectively and safely stop their TNFi therapy. Methods: The study was designed as a pragmatic multicenter, open‐label randomized controlled trial. Inclusion criteria were a diagnosis of RA according to the American College of Rheumatology 1987 classification criteria, as well as use of a TNFi for at least 1 year along with a stable dose of disease‐modifying antirheumatic drugs and a Disease Activity Score in 28 joints (DAS28) of <3.2 over the 6 months preceding trial inclusion. Patients were randomized in a 2:1 ratio to either stop or continue treatment with their current TNFi. Flare was defined as a DAS28 of ≥3.2 during the 12‐month follow‐up period and an increase in score of ≥0.6 compared to the baseline DAS28. Results: In total, 531 patients were allocated to the stop group and 286 to the TNFi continuation group. At 12 months, more patients had experienced a flare in the stop group (272 [51.2%] of 531) than in the continuation group (52 [18.2%] of 286; P  < 0.001). The hazard ratio for occurrence of a flare after stopping TNFi was 3.50 (95% confidence interval [95% CI] 2.60–4.72). The mean DAS28 in the stop group was significantly higher during the follow‐up period compared to that in the continuation group ( P  < 0.001). Of the 195 patients who restarted TNFi treatment after experiencing a flare and within 26 weeks after stopping, 165 (84.6%) had regained a DAS28 of <3.2 by 6 months later, and the median time to a regained DAS28 of <3.2 was 12 weeks (95% Cl 10.7–13.3). There were more hospitalizations in the stop group than in the continuation group (6.4% versus 2.4%). Conclusion: Stopping TNFi treatment results in substantially more flares than does continuation of TNFi in patients with established RA in remission or with stable low disease activity.